The Impact of High-Performance Human Resource Practices on Employees’ Attitudes and Behaviors - Kehoe, Rebecca R.; Wright, Patrick M. (Journal of Management, 2013)
Although strategic human resource (HR) management research has established a significant relationship between high-performance HR practices and firm-level financial and market outcomes, few studies have considered the important role of employees’ perceptions of HR practice use or examined the more proximal outcomes of high-performance HR practices that may play mediating roles in the HR practice–performance relationship. To address recent calls in the literature for an investigation of this nature, this study examined the relationships between employees’ perceptions of high-performance HR practice use in their job groups and employee absenteeism, intent to remain with the organization, and organizational citizenship behavior, dedicating a focus to the possible mediating role of affective organizational commitment in these relationships. Data in this study were collected from surveys of employees at a large multiunit food service organization. The model was tested with CWC(M) mediation analysis (i.e., centered within context with reintroduction of the subtracted means at Level 2), which accounted for the multilevel structure of the data. Results indicate that employees’ perceptions of high-performance HR practice use at the job group level positively related to all dependent variables and that affective organizational commitment partially mediated the relationship between HR practice perceptions and organizational citizenship behavior and fully mediated the relationship between HR practice perceptions and intent to remain with the organization. The discussion reviews the implications of these results and suggests future directions for research in this vein.